PENERAPAN METODE MIND MAPPING UNTUK MENINGKATKAN KETERAMPILAN MENULIS KARANGAN DESKRIPSI BAHASA INGGRIS PESERTA DIDIK KELAS X AP-1 SMK WIDYA MANDALA BADUNG - I Made Purna Wijaya (Kulturistik: Jurnal Ilmu Bahasa dan Budaya, 2018)
[Title: The Application of Mind Mapping Method to Improve Writing Skill in Writting English Descriptive Text of Students at Grades X AP-1 SMK Widya Mandala Badung] The aim of this paper is to determine students’ writing skill in doing descriptive. The research was conducted in the form of classroom action research, and mind mapping as learning method applied for improving students’writing skill. The application of this method in teaching and learning process arre expected to solve the problem that are faced by students at grade X AP1 SMK Widya Mandala. Constructivism theory were used to determine the learning model , in this case it has the same direction with mind mapping method. The theory of grammar and writing theory were used as a reference in making the assessment rubric. Methods of data collection and data analysis techniques performed quantitatively and qualitatively. Data were collected through a method of testing, observatiaon and questionnaires. The quantitative data collected through test and questionnaires, while the qualitative through observation. The result of the data analysis were presented in tables and charts with the description. The increased writing skill of the students can be seen from the average class grade, that is it is 63,7 in the pre-test, in the first cycle it became 73,9 and in the second cycle it became 78,3. The increased writing skill of the students is also proved by the increased percentage of grade achieved by the students that is more than 70. In the pre-test, the percentage of grade achieved was 33,33%, in the first cycle it became 59,26% and in the second cycle it became 100%.